Postpartum plasma profile of certain trace elements in Holstein Friesian cows with and without hormone therapy under tropical climate - PATEL, P M; DHAMI, A J; SAVALIYA, F P; RAMANI, V P (The Indian Journal of Animal Reproduction, 2023)
A total of 131 parous lactating cows were observed for postpartum ovarian activity and other estrual events from day 15 post-partum freshly calved HF cows (24) of University farm were monitored for weekly plasma profile and certain trace elements from the day of calving till 21" week postpartum with and without GnRH (Receptal) and PGF2a (Lutalyse) treatment at 71a week postpartum in anoestrus and suboestrus groups (6 each), respectively. The plasma zinc level ofanoestrus cows was significantly higher at calving (1.23 ± 0.06 vs 1.06 ± 0.05 ppm) and lower at 3rd week postpartum (1.03 ± 0.07 vs 1.3 I ± 0.08 ppm) than the suboestrus group. The weekly mean levels of zinc in GnRH and PGF2a treatment and pooled groups fluctuated significantly, whereas in their control groups it varied non-significantly between different weeks postpartum. The values were relatively high at calving till I week postpartum compared to other intervals with identical profile at most intervals in all the groups. The plasma iron levels in anoestrus and suboestrus groups varied insignificantly at all intervals postpartum, except at 121a, 17111 and 181a week, and the overall means (2.06 ± 0.05 vs 1.78 ± 0.05 ppm). The values were relatively low during early postpartum phase compared to 6 weeks later in all the groups, and did not differ significantly at any_ of the intervals postpartum, between treatment and control groups. The plasma copper concentration did not differ signifi• cantly at any of the intervals postpartum in GnRH and PGF2a groups, and even between their treatment and control groups, including the overall pooled means (0.81± 0.01 vs 0.76± 0.02 ppm). The levels in all groups, except GnRH control and PGF 2a treatment groups, varied significantly (P < 0.05) between different weeks postpartum in the range of0.61 ± 0.04 to 1.03 ± 0.04 ppm. The plasma cobalt and manganese concentration ofGnRH and PGF2a treatment, control and their pooled groups varied insignificantly between different weeks postpartum (0.31 ± 0.04 to 0.59 ± 0.04 and 0.05 ± 0.01 to 0.13 ± 0.03 ppm), and it did not differ significantly between groups at any of the intervals postpartum, except that copper was significantly higher at 201a week both in GnRH and PGF2a treatments than their control groups.